Pengaruh Media Pembelajaran Pop-Up Book Terhadap Minat Belajar Siswa Pada Mata Pelajaran IPA - Khaidir Fadil; Ratnasih Apriliani; Rusdi Kasman (STKIP Al Islam Tunas Bangsa dan HEPI, 2023)
The purpose of this study was to find out how interested fifth-grade students were in learning about science and to see if the use of Pop-Up Books as a learning tool had a big effect on students' interest in learning about science in class V. This study used a quasi-experimental design with a None-equivalent Control Group Design and a sampling method called